Numerical analysis of a microjet-based method for active flow control in convergent-divergent nozzles with a sudden expansion duct - Abid, Abdul; Khan, Sher Afghan; Baig, Muneer (Tech Science Press, 2022)
A method based on microjets is implemented to control the flow properties in a convergent-divergent nozzle undergoing a sudden expansion. Three different variants of this active control technique are explored numerically by means of a finite-volume method for compressible fluid flow: with the first one, the control is implemented at the base, with the second at the wall, while the third one may be regarded as a combination of the other two variants. When the jets are over-expanded, the control is not very effective. However, when a favorable pressure gradient is established at the nozzle, the control becomes effective, leading to an increase in the base pressure.